Pan-Cancer Exome-wide analysis of germline mutational patterns and pathways - Halima Alnaqbi; Michael Olbrich; Noora Zayed; Mira Mousa; Sarah Azzam; Syed Hammad Tirmazy; Habiba Alsafar (Scientific Reports)
Abstract Cancer progression and development are influenced by a complex interplay between inherited (germline) and acquired (somatic) mutations. Current cancer genomic research in Middle Eastern populations predominantly utilizes targeted panels to examine predefined genes, potentially overlooking a broader spectrum of genomic contributions to cancer predisposition. Addressing this gap, this study adopts an unbiased approach using whole exome sequencing (WES) data to identify both high- and low-penetrance genetic variants within the United Arab Emirates (UAE) population. This investigation features a case-control matching analysis comprising 62 patients diagnosed with various cancer types and 142 unrelated healthy controls. The results showed a potential association between cancer predisposition and variants within. The results demonstrate an association between cancer predisposition and variants within C-terminal Binding Protein 2 (CTBP2), DNA Polymerase Theta (POLQ) and Tektin 4 (TEKT4). Gene set enrichment analysis showed enriched pathways associated with cancer-related biological processes such as DNA repair and depleted pathways related to translation, cellular metabolic process, and mitochondrial functions. This study highlights that the distinctive genetic composition of underrepresented groups influences the penetrance of pathogenic variants that could contribute to hereditary cancer risk in ways that diverge from patterns observed in more extensively researched cohorts.